Identifikasi Penerapan Fitur Aplikasi Simrs Terhadap Efektivitas Pelayanan Pendaftaran Pasien Unit Rawat Jalan di RS X Kota Bandung - Salsabila Ananda Sephira; Ade Irma Suryani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Hospital Management Information System (HMIS) is a communication and information technology system that processes and integrates the whole steps of hospital’s service process in the form of a coordinated network, report and administration procedure to obtain information precisely and accurately. The purpose of this study is to determine the Identification of HMIS Application’s Features Implementation on the Effectivity of Outpatient’s Registration Service in Hospital X Bandung City. This study used descriptive method with qualitative approach which was carried out at Hospital X during March until April 2024 and as many as 4.373 outpatients who have registered to all available polyclinics. The subjects of this study consisted of the head of the medical record unit, 2 registration operators and IT technicians. The results obtained from this study is that the HMIS application at Hospital X hasn’t been running effectively due to often constraint of errors on the HMIS application that being used by Hospital X which also has been connected to BPJS by bridging method till it causes constraints to medical record officers and IT technicians during the registration of the patients along with no exclusive training regarding HMIS application for new employees.